The Role of Recreational Sports in Promoting Mental Health among Adolescents - Dupont, Claire (International Journal of Arts, Recreation and Sports, 2024)
Purpose: The general objective of this study was to investigate the role of recreational sports in promoting mental health among adolescents. Methodology: The study adopted a desktop research methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive’s time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The findings reveal that there exists a contextual and methodological gap relating to the role of recreational sports in promoting mental health among adolescents. Preliminary empirical review revealed that recreational sports had a significant positive impact on the mental health of adolescents, reducing depression and anxiety while enhancing self-esteem and social belonging. It emphasized the importance of structured sports programs in providing safe, supportive environments that fostered essential life skills and resilience. The study also highlighted the need for further research on the long-term effects and the influence of socio-cultural factors on sports participation outcomes. Overall, it recommended prioritizing recreational sports programs to promote mental health and well-being among adolescents. Unique Contribution to Theory, Practice and Policy: The Self- Determination Theory, Social Cognitive Theory and Ecological Systems Theory may be used to anchor future studies on recreational sports and the mental health of adolescents. The study highlighted the importance of integrating multidisciplinary theoretical frameworks to understand how recreational sports promote adolescent mental health, recommending the use of theories such as Self-Determination Theory, Social Cognitive Theory, and Ecological Systems Theory. It emphasized the need for structured, inclusive sports programs in schools, training for coaches on mental health issues, and policies that ensure equitable access to sports activities. The study also called for the integration of mental health education within sports programs, longitudinal research to evaluate long-term effects, and community engagement to support and sustain these initiatives.